Tuesdays with Morrie : an old man, a young man, and life's greatest lesson - Albom, Mitch, 1958- (Doubleday, 1997)
Maybe it was a grandparent, or a teacher or a colleague.Someone older, patient and wise, who understood you when you were young and searching, and gave you sound advice to help you make your way through it.For Mitch Albom, that person was Morrie Schwartz, his college professor from nearly twenty years ago.Maybe, like Mitch, you lost track of this mentor as you made your way, and the insights faded.Wouldn't you like to see that person again, ask the bigger questions that still haunt you? Mitch Albom had that second chance. He rediscovered Morrie in the last months of the older man's life.Knowing he was dying of ALS - or motor neurone disease - Mitch visited Morrie in his study every Tuesday, just as they used to back in college.Their rekindled relationship turned into one final 'class': lessons in how to live.